A Review on Compressive Strength of Concrete Containing Waste Cathode Ray Tube Glass as Aggregates - Nurul Noraziemah Mohd Pauzi (Civil and Sustainable Urban Engineering, 2021)
The issue of the cathode ray tube (CRT) technology facing its end-of-time and increasing quantities across the globe has acquired the responsiveness of many researchers. The use of waste CRT glass as a construction material has fascinated them due to its significant advantage in recycling the hazardous and non-biodegradable waste CRT glass. However, lack of knowledge about the effects and features of CRT glass as a construction material could be a hindrance to the excessive utilization of waste CRT glass. Therefore, in order to establish the idea of using CRT waste glass as a more common construction material, this paper reviews several recycling techniques of CRT glass and further detail on the workability, density, and compressive strength properties of concrete and mortar using CRT glass (treated or untreated) as fine aggregates. The review showed that, generally, the use of CRT glass as a complete or partial replacement of natural sand shows a slight increase in density, workability, and concrete strength compared to conventional concrete. However, there are no clear trends that can be concluded as this review also showed that various factors influenced its performance, such as percentage replacement, particle size, lead (Pb) content, and types of admixtures.